Settler Children, Kangaroos and the Cultural Politics of Australian National Belonging. Issue 3 (September 2014) - Taylor, Affrica
This article reflects upon the ways in which white settler children and kangaroos were enlisted into the cultural politics of nation-building and belonging in the early days of Australian Federation. It revisits Ethel Pedley's turn-of-the-century children's book, Dot and the Kangaroo, and contextualises it within some of the notable kangaroo/settler events within Australia's colonial history. It draws attention to the paradoxes inherent in the symbolic association of settler children with native Australian animals in the emerging national imaginary. The article brings early Australian children's literature into conversation with settler colonial critique and the 'animal turn'.